5-HT interaction with other neurotransmitters : experimental evidence and therapeutic relevance. - Di Giovanni, Giuseppe; Deurwaerdere, Philippe de (Progress in brain research, 2021)
The Progress in Brain Research series highlights new advances in the field, with this new volume presenting interesting chapters. Each chapter is written by an international board of authors.